Agro-economic performance of dual purpose barley (Hordeum vulgare L.) vartieties under varying seed rate and fertility levels - Singh, Dilip; Singh, D. R.; Nepalia, V.; Kumari, Amina (Annals of Agricultural Research, 2016)
In order to select best suited dual purpose barley variety, to work out optimum fertilizer levels and seed rate, a field experiment was conducted during rabi 2009-10. The treatment consisted combinations of two dual purpose varieties (RD 2552 and RD 2035), three seed rate (100, 125 and 150 kg/ ha) and three fertilizer levels (100 per cent RDF: 60 + 20 kg N + P2O5 /ha, 125 per cent RDF and 150 per cent RDF). Green fodder yield and growth character of dual purpose barley variety RD 2552 before and after green fodder cutting was significantly higher over RD 2035. The variety had higher grain and straw yield, accumulated maximum N and P in green fodder, grain and straw and total uptake compared to variety RD 2035. This manifested in additional net returns of Rs.4958 ha- 1 over RD 2035 and increased B:C ratio from 1.4 to 1.7. Application of 125 kg seed/ ha proved best and economically profitable over 100 kg seed/ha. The results revealed that application of 125 and 150 per cent RDF improved growth parameters, yield attributing parameters, grain, straw yield, N and P uptake over 100 per cent RDF. Protein content increased and crude fibre content of green fodder decreased with increasing fertility levels. However, TDN remains stable under varying fertility levels. With highest net returns and B:C ratio application of 125 per cent RDF proved most economically beneficial.